Prune belly syndrome: a South African perspective - Leahy, Shannon D; Kala, Udai; Petersen, Karen L (African Journal of Nephrology, 2018)
Background: Prune belly syndrome (PBS) is a rare congenital disorder with a triad of signs: absent abdominal wall musculature, urinary tract malformations, and cryptorchidism. The aims of this study were to describe the epidemiology, renal function, management and outcome of patients with PBS at the Chris Hani Baragwanath Academic Hospital, Johannesburg, South Africa. Methods: A retrospective record review was conducted of patients with PBS referred to the paediatric nephrology unit from 1984 to 2014. Results: A total of 44 patient records were analysed. Most of the patients presented as neonates (n = 35, 80%). The accompanying congenital malformations included urological problems (21, 48%), orthopaedic abnormalities (5, 11%), congenital heart disease (3, 7%) and gastrointestinal abnormalities (2, 4%). The medical management included the use of prophylactic antibiotics and intermittent bladder catheterisation. Surgical management included abdominoplasty with orchidopexy and circumcision. At the last clinic visit, severe reductions in renal function were noted in 11 (58%) of the patients under the age of 2 years, whereas normal renal function was present in 14 (56%) of the patients over 2 years of age. The default rate was 57%; 6 (14%) patients were transferred to an adult clinic and 2 (4%) patients died. Conclusions: The patient profiles and the management recorded are comparable with other reported series. There are differences in the frequencies of congenital malformations and the rates of surgical intervention. The renal outcome for children older than two years was favourable compared to younger children. Progression to end-stage renal disease was observed infrequently, but this may be underestimated in view of the high default rate.